Healthcare professionals’ views on healthcare-related factors influencing symptom course in persistent somatic symptoms: a qualitative study of four European countries - Aleksandra Kustra-Mulder; Brodie McGhie-Fraser; Tara Petzke; Karolina Fila-Pawłowska; Judith Rosmalen; Fiammetta Cosci; Bernd Löwe; Angelika Weigel (BMC Health Services Research)
Abstract Background The care trajectory for patients with Persistent Somatic Symptoms (PSS) is complex due to variability in diagnoses and treatments, with differences across European healthcare systems. Existing findings predominantly come from individual Western European countries, and comparative studies are lacking. This study aimed to explore how healthcare systems are perceived to influence PSS courses across four European countries and how professionals view their respective systems regarding PSS. Methods We used semi-structured interviews to conduct a qualitative study with healthcare professionals from Germany, Italy, the Netherlands, and Poland. Sixteen participants were recruited purposively through international and national networks focusing on PSS, ensuring representation from primary care, secondary care medical specialists, mental health, and other healthcare fields. Results We found that the interaction of structural and interpersonal factors within the healthcare system influenced the course of PSS symptoms. Systemic barriers such as limited consultation times and issues in care pathways or insurance coverage were prevalent in Germany and the Netherlands, while access and trust issues were more prominent in Italy and Poland. Key improvements suggested included reimbursement and treatment eligibility for PSS, establishing collaborative care pathways, and sufficient consultation times. Additionally, enhancing professional-patient relationships and improving education for healthcare professionals and patients were identified as crucial steps. Conclusions The results show that although expertise is improving, current healthcare system structures prevent professionals from using them effectively. Therefore, systemic reforms and better professional training are needed to improve care for patients with PSS.